First record of endoparasite infestation in low value fish food in East Java, Indonesia - Attabik Mukhammad Amrillah; Julian Ransangan; Syaifullah; Mohammad Tamrin Mohamad Lal (Faculty of Science, Ain Shams University, Abbasia, Cairo, 2025)
This research was conducted in Jawa Timur to provide information on the infestation of endoparasites in mackerel fish used as feed for grouper aquaculture. Low-value fish specimens were randomly collected from fish traders in the Karangploso market. These specimens were then analyzed in the laboratory. During collection, the specimens were stored in ice to maintain their integrity. Morphological measurements, including body weight and total length, were recorded, and the presence of parasites was observed. A total of 78 samples were collected and classified into two groups based on morphological observations: the yellowtail scad (Atule sp., n = 43) and the Indian mackerel (Rastrelliger sp.; n = 35). The length and weight of the samples were appropriate for use as feed. The prevalence of parasitic worms was found to be 7% in the yellowtail scad, categorizing it as an occasional infection. In contrast, no parasitic worms were detected in the Indian mackerel, classifying it as rare infection. Based on these findings, the two types of fish found in East Java are relatively healthy and suitable for use as feed for cultured grouper.